Electrospun fibers and sorbents as a possible basis for effective composite wound dressings - Saul Alvarez-Suarez, Alan; Dastager, Syed G.; Bogdanchikova, Nina; Grande, Daniel; Pestryakov, Alexey; Carlos Garcia-Ramos, Juan; Lizeth Perez-Gonzalez, Graciela; Juarez-Moreno, Karla; Toledano-Magana, Yanis; Smolentseva, Elena; Antonio Paz-Gonzalez, Juan; Popova, Tatiana; et al. (Micromachines, 2020)
Skin burns and ulcers are considered hard-to-heal wounds due to their high infection risk. For this reason, designing new options for wound dressings is a growing need. The objective of this work is to investigate the properties of poly (epsilon-caprolactone)/poly (vinyl-pyrrolidone) (PCL/PVP) microfibers produced via electrospinning along with sorbents loaded with Argovit (TM) silver nanoparticles (Ag-Si/Al2O3) as constituent components for composite wound dressings. The physicochemical properties of the fibers and sorbents were characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and inductively coupled plasma optical emission spectroscopy (ICP-OES). The mechanical properties of the fibers were also evaluated. The results of this work showed that the tested fibrous scaffolds have melting temperatures suitable for wound dressings design (58-60 degrees C). In addition, they demonstrated to be stable even after seven days in physiological solution, showing no macroscopic damage due to PVP release at the microscopic scale. Pelletized sorbents with the higher particle size demonstrated to have the best water uptake capabilities. Both, fibers and sorbents showed antimicrobial activity against Gram-negative bacteria Pseudomona aeruginosa and Escherichia coli, Gram-positive Staphylococcus aureus and the fungus Candida albicans. The best physicochemical properties were obtained with a scaffold produced with a PCL/PVP ratio of 85:15, this polymeric scaffold demonstrated the most antimicrobial activity without affecting the cell viability of human fibroblast. Pelletized Ag/Si-Al2O3-3 sorbent possessed the best water uptake capability and the higher antimicrobial activity, over time between all the sorbents tested. The combination of PCL/PVP 85:15 microfibers with the chosen Ag/Si-Al2O3-3 sorbent will be used in the following work for creation of wound dressings possessing exudate retention, biocompatibility and antimicrobial activity.
Keywords: electrospinning; poly (epsilon-caprolactone); poly (vinyl pyrrolidone); silver sorbents; wound dressings

Comparative study of polycaprolactone electrospun fibers and casting films enriched with carbon and nitrogen sources and their potential use in water bioremediation - Alejandra Pompa-Monroy, Daniella; Leticia Iglesias, Ana; Gulam Dastager, Syed; Namdeo Thorat, Meghana; Olivas-Sarabia, Amelia; Valdez-Castro, Ricardo; Angelica Hurtado-Ayala, Lilia; Manuel Cornejo-Bravo, Jose; Lizeth Perez-Gonzalez, Graciela; Jesus Villarreal-Gomez, Luis (Membranes, 2022)
Augmenting bacterial growth is of great interest to the biotechnological industry. Hence, the effect of poly (caprolactone) fibrous scaffolds to promote the growth of different bacterial strains of biological and industrial interest was evaluated. Furthermore, different types of carbon (glucose, fructose, lactose and galactose) and nitrogen sources (yeast extract, glycine, peptone and urea) were added to the scaffold to determinate their influence in bacterial growth. Bacterial growth was observed by scanning electron microscopy; thermal characteristics were also evaluated; bacterial cell growth was measured by ultraviolet-visible spectrophotometry at 600-nm. Fibers produced have an average diameter between 313 to 766 nm, with 44% superficial porosity of the scaffolds, a glass transition around similar to 64 degrees C and a critical temperature of similar to 338 degrees C. The fibrous scaffold increased the cell growth of Escherichia coli by 23% at 72 h, while Pseudomonas aeruginosa and Staphylococcus aureus increased by 36% and 95% respectively at 48 h, when compared to the normal growth of their respective bacterial cultures. However, no significant difference in bacterial growth between the scaffolds and the casted films could be observed. Cell growth depended on a combination of several factors: type of bacteria, carbon or nitrogen sources, casted films or 3D scaffolds. Microscopy showed traces of a biofilm formation around 3 h in culture of P. aeruginosa. Water bioremediation studies showed that P. aeruginosa on poly (caprolactone)/Glucose fibers was effective in removing 87% of chromium in 8 h.
Keywords: bacterial growth; carbon source; electrospinning; nitrogen source; poly (caprolactone)